Hydrodynamics of Uasb Reactor Treating Domestic Wastewater: A Three-Dimensional Numerical Study - Maria G. S. L. Brito (Water, 2020)
This work performed a three-dimensional numerical study to describe the hydrodynamics of upflow anaerobic sludge blanket reactor treating domestic wastewater. The simulations were made in the commercial software Ansys CFX®. Different inclinations of the gas deflector were considered, to assess its influence on the velocity field inside the reactor. In order to validate the numerical study, we used experimental data regarding the inflow, the inlet and outlet concentrations of the organic matter, the concentration of solids at the liquid-gas interface and at the reactor outlet, and the pressure field inside it. The comparison between the numerical and experimental results demonstrated small differences. The mathematical model used to describe the hydrodynamics flow in the UASB reactor was quite satisfactory since it adequately has reproduced the physical behavior inside the reactor.